2013
DOI: 10.1016/j.actbio.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Micromotion-induced strain fields influence early stages of repair at bone–implant interfaces

Abstract: Implant loading can create micromotion at the bone-implant interface. The interfacial strain associated with implant micromotion could contribute to regulating the tissue healing response. Excessive micromotion can lead to fibrous encapsulation and implant loosening. Our objective was to characterize the influence of interfacial strain on bone regeneration around implants in mouse tibiae. A micromotion system was used to create strain under conditions of (1) no initial contact between implant and bone, and (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 34 publications
5
86
1
1
Order By: Relevance
“…[21][22][23][24] Therefore, future studies should be performed to assess the effects of these medications on the load-bearing ability of the interface, associated with micromotions applied transcutaneously to the implants during bone repair. Similar studies have been performed previously by Wazen et al 25 Currently, there are no reports in the literature showing statistically significant differences among osteoporotic patients rehabilitated with dental implants. In addition, there are no statistical reports regarding the failure rate of this treatment.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[21][22][23][24] Therefore, future studies should be performed to assess the effects of these medications on the load-bearing ability of the interface, associated with micromotions applied transcutaneously to the implants during bone repair. Similar studies have been performed previously by Wazen et al 25 Currently, there are no reports in the literature showing statistically significant differences among osteoporotic patients rehabilitated with dental implants. In addition, there are no statistical reports regarding the failure rate of this treatment.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, taken together with the previous results, the present study highlights the need for further in vivo investigations of load-bearing implants. 25 The animal model used in the present study was used previously by Glosel et al 31 They reported that, according to the United States Food and Drug Administration (FDA), female rats at 3 months after a bilateral OVX represent the ideal model to mimic postmenopausal osteoporosis. 31 The combination of OVX with a low Ca 2+ and PO 4À diet was first reported by Teófilo et al 5 This model has been effective in simulating osteoporosis in rats, with a two-fold reduction in bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…However, attributable in part to PEEK's relatively inert and hydrophobic surface, recent evidence has demonstrated that smooth PEEK can exhibit poor osseointegration [9,25] and fibrous capsule formation around the implant [23,34]. Lack of bone-implant contact can induce micromotion and inflammation that leads to fibrous layer thickening, osteolysis, and implant loosening [2,13,29,37,48]. Previous studies [1,4,15,16,18,36] have shown that surface modifications such as plasma treatments, coatings, and composites can improve PEEK implant integration, yet many suffer practical limitations such as delamination, instability, and mechanical property tradeoffs.…”
Section: Introductionmentioning
confidence: 99%
“…Using this information we have identified principal strains in the 10–20% range to stimulate osseointegration [13,14]. Genetic mouse models have been particularly helpful in identifying key variables that influence osseointegration; namely, we demonstrated that early excessive micromotion can cause fibrous encapsulation [15] and the elimination of mechanically sensitive cellular appendages such as primary cilia can obliterate the strain-induced bone formation [16,17]. …”
Section: Introductionmentioning
confidence: 99%